Finding Nemo (Parrogon Books Ltd, 2014)
When his son, Nemo, is captured by a driver in the Great Barrier Reef, Marlin stops at nothing to rescue him. Together with his new friends Dory, they set off on a dangerous journey.
Keywords: Animal Stories